Interaction of CH3O2 radicals with CH3CHO and CH4 on TiO2 surface - I. A. Vardanyan; L. A. Manucharova; H. A. Jalali; S. V. Tsarukyan (ՀՀ ԳԱԱ հրատ.)
The reaction of CH3O2 radicals with CH4 and CH3CHO on TiO2 (rutile) surface at room temperature has been studied. It was shown that in both cases the radicals multiplication has been observed. This phenomenon was ascribed to the additional consumption of organic compound by the chain branching mechanism initiated by above mentioned reaction. CH3CHO և CH4 օրինակի վրա ուսումնասիրվել է օրգանական միացության հետ CH3O2 ռադիկալների հետերոգեն ռեակցիան: Ցույց է տրված, որ երկու դեպքում էլ դիտվում է ռադիկալների բազմացման երևույթը, որը պայմանավորված է օրգանական միացության ծախսով շղթայական ճյուղավորված մեխանիզմով`հարուցված վերոհիշյալ ռեակցիայով: На примере ацетальдегида и метана на поверхности TiO2 изучено влияние природы органического соединения на реакцию CH3O2 радикалов с органическим соединением. Показано, что в обоих случаях наблюдается явление размножения радикалов, которое объясняется инициированием вышеуказанной реакцией расходования органического соединения по цепному разветвленному механизму.
Keywords: Organic Chemistry